Effectiveness Of Bidara (Ziziphus mauritiana) Extract On The Long Wound Healing In White Rats (Rattus norvegicus) - Ariani, Novida; Kalsum, Umi; Maria Marpaung, Charlie Angel (International Journal of Health Engineering and Technology, 2023)
Bidara have active compounds which affects in regenerating and repairing the skin’s epidermal layer. Examine the benefits of bidara (Ziziphus mauritiana) as a wounds cut treatment on white rats (Rattus Norvegicus). The type of research is quantitative research. Data collection using an observation of the length of wound healing in days and indicators of wound healing. The average wound healing time data was normally distributed and homogeneous with p>0.05. One Way ANOVA resulted p=0.16 means there is no difference between groups. Wound healing indicator data with the Nagaoka scale reached a p>0.05 means the data normally distributed and homogeneous. One Way ANOVA gave a value of p=0.00 means there is significant difference between groups and continued with Post Hoc and T-Test. The comparison of average wound healing time between groups with the intervention of 8% bidara extract ointment, 16%, and 25% influenced by the diversity. The administration of bidara extract ointment can be an alternative in post-incision wound care in obstetrics cases